Antibacterial activity mechanism of coptisine against Pasteurella multocida - Zhang, Rui; Tian, Shuo; Zhang, Tengfei; Zhang, Wenting; Lu, Qin; Hu, Qiao; Shao, Huabin; Guo, Yunqing; Luo, Qingping (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Pasteurella multocida is a widespread zoonotic pathogen that causes severe damage to the poultry industry. This study focused on the antibacterial effects and mechanism of action of coptisine against P. multocida. Methods The minimum inhibitory concentration and half maximal inhibitory concentration of coptisine against P. multocida was measured. Additionally, the effect of coptisine on growth, cell wall, activity of respiratory enzymes, soluble protein content and DNA synthesis were also analyzed. Finally, the effect of coptisine on gene transcription was determined using RNA sequencing. Results We demonstrated that coptisine has a strong antibacterial effect against P. multocida, with a minimum inhibitory concentration of 0.125 mg/mL. Moreover, the measurement of the half maximal inhibitory concentration confirmed that coptisine was safe for the pathogen. The growth curve showed that coptisine inhibited bacterial growth. Measurement of alkaline phosphatase activity in the culture solution showed that coptisine affected cell wall permeability. Transmission electron microscopy revealed that coptisine chloride destroyed the cell structure. In addition, coptisine blocked the respiratory system, as measured by the levels of critical enzymes of the tricarboxylic acid cycle and glycolysis, succinate dehydrogenase and lactate dehydrogenase, respectively. Similarly, coptisine inhibited the synthesis of soluble proteins and genomic DNA. The KEGG pathway analysis of the differentially expressed genes showed that they were associated with cellular, respiratory, and amino acid metabolism, which were downregulated after coptisine treatment. Additionally, genes related to RNA degradation and the aminoacyl-tRNA pathway were upregulated. Conclusion In this study, we demonstrated that coptisine exerts an antibacterial effect on P. multocida. These findings suggest that coptisine has a multifaceted impact on various pathways, resulting in the inhibition of P. multocida. Thus, coptisine is a potential alternative to antibiotics for the treatment of P. multocida infections in a clinical setting.